Emergency Medicine Residents' Self‐assessments Play a Critical Role When Receiving Feedback. (15th October 2013) - Bounds, Richard; Bush, Colleen; Aghera, Amish; Rodriguez, Nestor; Stansfield, R. Brent; Santen, Sally A.; Yarris, Lalena
Abstract Objectives Emergency medicine (EM) faculty often aim to improve resident performance by enhancing the quality and delivery of feedback. The acceptance and integration of external feedback is influenced by multiple factors. However, it is interpreted through the "lens" of the learner's own self‐assessment. Ideally, following an educational activity with feedback, a learner should be able to generate and act upon specific learning goals to improve performance. Examining the source of generated learning goals, whether from one's self‐assessment or from external feedback, might shed light on the factors that lead to improvement and guide educational initiatives. Using a standard oral board scenario, the objective of this study was to determine the effects that residents' self‐assessment and specific feedback from faculty have on not only the generation of learning goals but also the execution of these goals for performance improvement. Methods In this cross‐sectional educational study at four academic programs, 72 senior EM residents participated in a standardized oral board scenario. Following the scenario, residents completed a self‐assessment form. Next, examiners used a standardized checklist to provide both positive and negative feedback. Subsequently, residents were asked to generate "SMART" learning goals (specific, measurable, attainable, realistic, and time‐bound). The investigators categorized the learning goals as stemming from the residents' self‐assessments, feedback, or both. Within 4 weeks, the residents were asked to recall their learning goals and describe any actions taken to achieve those goals. These were grouped into similar categories. Descriptive statistics were used to summarize the data. Results A total of 226 learning goals were initially generated (mean ± SD = 3.1 ± 1.3 per resident). Forty‐seven percent of the learning goals were generated by the residents' self‐assessments only, while 27% were generated by the feedback given alone. Residents who performed poorly on the case incorporated feedback more often than high performers when generating learning goals. Follow‐up data collection showed that 62 residents recalled 89 learning goals, of which 52 were acted upon. On follow‐up, the numbers of learning goals from self‐assessment and feedback were equal (25% each, 13 of 52), while the greatest number of reportedly executed learning goals came from self‐assessments and feedback in agreement (40%). Conclusions Following feedback on an oral board scenario, residents generated the majority of their learning goals from their own self‐assessments. Conversely, at the follow‐up period, they recalled an increased number of learning goals stemming from feedback, while the largest proportion of learning goals acted upon stemmed from both feedback and self‐assessments in agreement. This suggests that educators need to incorporate residents' self‐assessments into any delivered feedback to have the greatest influence on future learning goals and actions taken to improve performance.